Association of Serum Inflammatory Factors and Hematologic Parameters With Lower Limb Deep Vein Thrombosis in Neurocritical Patients: A Retrospective Cohort Study - Zhu, Yunqiu; Wang, Chun; Wang, Jia; Shi, Tian; Tang, Weijie; Zhou, Huaping; Guo, Wanfei; Mei, Hongbin; Bo, Jinxiang (Journal of Medical Biochemistry, 2025)
Objective: The aim of this study was to investigate the mechanisms of postoperative deep vein thrombosis (DVT) of the lower extremities in neurocritical care patients, focusing on the interaction of inflammatory factors [D-dimer (DD), prothrombin time (PT), blood cell parameters (lymphocytes, platelets, plateletcrit) and coagulation function.Methods: A retrospective cohort study design was used to include 261 neurocritical care patients who underwent surgery between August 2019 and August 2021. They were categorized into DVT group (n=121) and non-DVT group (n=140) based on postoperative lower limb Doppler ultrasound findings. Preoperative coagulation indices (TT, DD), inflammatory markers [C reactive protein (CRP), procalcitonin (PCT), fibrinogen (FIB)], and blood cell parameters (hemoglobin, neutrophils, lymphocytes, platelet counts, and plateletcrit) were collected from the patients.Results: DD levels were significantly higher and TT shorter in the DVT group than in the non-DVT group (P
Keywords: neurocritical care; Deep Vein Thrombosis; immunothrombosis; D-dimer